Causes Of Poor English Academic Performance: A Survey Of EFL Students at an Islamic Boarding School in Kampar - Nurul Defitri; Bukhori Bukhori (Kutubkhanah, 2023)
This research investigated the causes of poor English students' academic performance at one of Islamic boarding school in Kampar. The survey was used as design of the research. 46 students were selected purposively as the sample out of 184 students of second year of senior high school of an Islamic boarding school in Kampar. Questionnaire was used to collect the data and descriptive statistic was used to analyze the data. This research found that there were three factors that caused of poor English students’ academic performance namely: mother tongue, unavailable qualified English teacher, and lack of facilities in learning English. Out of three factors, dominance of mother tongue and lack of facilities in learning English could be determined as the dominant factors.